Route and strategies for implementing active methodologies in a higher education institution (Research, Society and Development, 2020)
A cross-sectional prospective design study with a qualitative approach conducted with four professors from a University Center in Rio de Janeiro responsibles for the process of implementing Active Methodologies at the Institution's Health School. The objective of this study was to present the path of the implementation of active methodologies as a guiding basis of the teaching-learning process. Semi-structured interviews were conducted in August and September, 2019 with professors in management positions. Participants reported not having previous experience with active methodologies and highlighted immersion courses and webnais for teachers as an academic strategy. Despite evidence of initial resistance from some teachers, participants report acquiescence and adequacy in practical daily life recognizing the effectiveness of active methodologies as a guiding thread in the teaching-learning process of this higher education institution.